Publikasi Poster Pencegahan Covid-19 di Desa Sukajadi, Kabupaten Ciamis Sebagai Upaya Pencegahan Covid-19 - Krisna Mahardika; Muh. Sulaiman Dadiono (Abdi Jaya : Jurnal Pengabdian Indonesia, 2025)
The increase in Covid-19 is due to low public awareness of prevention efforts. The solution that can be provided is to socialize the prevention of Covid-19 and disseminate information about Covid-19 through poster media distributed via Instagram and WhatsApp, especially in Sukajadi Village, Ciamis Regency as one of the Thematic KKN programs. The purpose of the Covid-19 prevention poster publication activity and updates on the number of Covid-19 exposures is to increase public awareness, especially in Sukajadi Village, Ciamis, regarding the prevention of Covid-19. The method used is the Participatory Rural Appraisal method and survey. The results of this activity can increase the awareness of Sukajadi Village of the importance of preventing Covid-19.